Aplikasi Transaksi Bisnis Usaha Mikro Kecil dan Menengah dengan Fitur Penyimpanan Data Online dan Offline - Michelle Florensia; Silvia Rostianingsih; Andreas Handojo (Jurnal Infra, 2021)
Micro Small and Medium Enterprises (MSMEs) today are still many who do manual recording using paper so that often causes miscalculation. In addition, MSMEs are also unable to provide information quickly because information is not distributed. MSME actors also need time in analyzing sales. Therefore, a system is needed that can help MSMEs to record and calculate stocks and profit/loss statementsSeeing the problem, then this thesis will be created a website with the feature of recording goods, buying and selling transactions, and the calculation of profit/loss. In addition, the website is equipped with online and offline data storage features so that users do not have to be connected to the internet. The system is made based on a website so that MSMEs can access the website through a smartphone or laptop. The system will be created using the PHP 7 programming language, download the cache using the Service Worker as well as use the CouchDB online database and the PouchDB offline database.Based on the results of this thesis research can be concluded that the use of the website can help MSMEs in recording the business process. Websites can also run without an internet connection, but pages must be loaded one by one. Memory usage is also small enough that it does not interfere with the performance of the device. This website can be developed further by adding features and easier to do cache downloads